Somatic maturation and body composition in female healthy adolescents with or without adjustment for body fat - Miranda, Valter Paulo N. (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To evaluate the relationship between the stages of somatic maturation and body composition in eutrophic female adolescents with or without excessive body fat. METHODS: Cross-sectional study of 118 female adolescents, from 14 to 19 years-old, in Viçosa, Minas Gerais, Southeast Brazil. The adolescents were divided in two groups: Group 1 (G1), eutrophic with adequate body fat percentage, and Group 2 (G2), eutrophic with high body fat percentage. The somatic maturation was assessed by the formula for estimating the Peak Height Velocity (PHV). RESULTS: The PHV had higher average score in G1 adolescents compared to G2 (0.26 versus 0.05; p=0.032). There was an association between G1, G2 and the somatic maturation (p=0.049). The female adolescents before and during PHV presented higher values of fat body BMI (p=0.034) and percentage of central fat (p=0.039) compared to the adolescents after PHV. There was a correspondence between before PHV stage and the excess of body fat (α=0.751). CONCLUSIONS: There was an association between somatic maturation and body composition in eutrophic female adolescents. Length, BMI and fat percentage were different among the somatic maturation stages. It is relevant to evaluate the somatic maturation and the changes occurring in the body composition during adolescence in order to better evaluate and manage the nutritional status and the body fat excess.